Claiming the international (2013)
This book explores the possibilities of alternative worldings beyond those authorized by the disciplinary norms and customs of International Relations. In response to the boundary-drawing practices of IR that privilege the historical experience and scholarly folkways of the "West," the contributors examine the limits of even critical practice within the discipline; investigate alternative archives from India, the Caribbean, the steppes of Eurasia, the Andes, China, Japan and Southeast Asia that offer different understandings of proper rule, the relationality of identities and polities, notions of freedom and imaginations of layers of sovereignty; and demonstrate distinct modes of writing and inquiry. In doing so, the book also speaks about different possibilities for IR and for inquiry without it.